The Different Concentrations of Transforming Growth Factor-Beta1 (TGF-Beta1), Matrix Metalloproteinase-9 (MMP-9) and Vascular Endothelial Growth Factor Receptor-2 (VEGFR-2) in Normoalbuminuria Normotension, Normoalbuminuria Hypertension - Johnson Wijaya; Marsetio Donosepoetro; Syakib Bakri (The Prodia Education and Research Institute (PERI), 2009)
BACKGROUND: Vascular remodeling was an adaptive process of the vascular wall that occured in response to long-term changes in hemodynamic conditions that contribute to the changes of the vascular structure and the pathophysiology of vascular disease. On the other hand, Endothelial Progenitor Cells (EPC) derived from bone marrow had the capacity to migrate to the peripheral circulation and to differentiate into mature endothelial cells. Therefore, EPC could contribute in the endothelial repairing after endothelial injury.METHODS: This study was a cross sectional design. Analysis was done among 30 subjects with normoalbuminuria normotension, 55 subjects with normoalbuminuria hypertension and 30 subjects with with microalbuminuria hypertension. TGF-β1, MMP-9 and VEGFR-2 testing were performed by ELISA method. All statistical calculations were performed using the SPSS 11.5 statistical software package. We used the Independent sample T test, Mann-Whitney, One Way Annova and Kruskal Wallis to establish the difference among various biochemical measures.RESULTS: TGF-β1 concentration was increased from normoalbuminuria normotension to normoalbuminuria hypertension and to microalbuminuria hypertension (27.63178±12.97246 vs. 38.61193±17.09546 vs. 38.73939±12.63911 ng/mL). TGF-β1 concentration was higher significantly in normotension as compared to hypertension (27.63178±12.97246 vs. 38.65692±15.58950, p<0.001) and to microalbuminuria hypertension (38.73939±12.63911, p<0.001). MMP-9 concentration was increased in normotension to normoalbuminuria hypertension but was decreased in microalbuminuria hypertension (438.1967±156.4268 vs. 564.5873±291.2876 vs. 418.6900±188.3801 ng/mL). MMP-9 concentration was higher significantly in normoalbuminuria hypertension as compared to microalbuminuria hypertension (p=0.028). VEGFR-2 concentration was decreased from normotension to normoalbuminuria hypertension to microalbuminuria hypertension (9.90552±1.85185 vs. 9.39561±1.75413 vs. 9.00506±1.47173 ng/mL). VEGFR-2 concentration was higher significantly in normotension as compared to microalbuminuria hypertension (p=0.042). CONCLUSIONS: The increasing concentration level of TGF-β1 and decreasing concentration level of MMP-9 in microalbuminuria hypertension showed that the remodeling process was getting increased. The decreasing concentration level of VEGFR-2 in microalbuminuria hypertension showed that the repairing process was getting decreased.KEYWORDS: vascular remodelling, vascular repairing, TGF-β1, MMP-9, VEGFR-2